Retrieving Sources in the Digital Age: Information Literacy Skills among Moroccan English Department Students - IDABDALLAH, Abdelhadi (International Journal of Language and Literary Studies, 2025)
This study examines the development of source retrieval skills among students in the English department at Moroccan universities. It draws on data from the Standardized Assessment of Information Literacy Skills (SAILS) test. This research aims to identify the performance trends of students and instructional gaps related to the skill of retrieving sources. The population is undergraduate, master’s, and doctoral students. Descriptive and ANOVA analyses revealed variation among the groups. The doctoral students outperformed the others but still demonstrated moderate proficiency in general. The weaknesses across all levels highlight primarily the limited integration of information literacy skills into English studies curricula. Therefore, the findings indicate that there is a tendency for retrieving source skills to improve with academic progression; however, they are often acquired through faculty’s informal practices rather than through structured instruction. This means that these gains are only marginal and unsystematic. The findings also emphasize the need for targeted and specific pedagogical interventions and closer collaboration between faculty and librarians to maximise the students’ research competencies. As it shows on Moroccan policy documents, this study also situates these challenges within the country’s efforts to enhance digital and academic literacy in higher education.